60 Examining the impact of obesity ≥30 kg/m2 on acute kidney injury following cardiac surgery. (7th October 2015) - O'Sullivan, K; Byrne, JS; Hudson, A; Murphy, AM; Sadlier, D; Hurley, JP
Abstract : Background: Postoperative acute kidney injury (AKI) is a frequent and serious consequence of cardiac surgery. A complex and multifactorial issue, improved understanding of its aetiological components will aid development of preventative strategies prospectively. The global prevalence of obesity has reached epidemic proportions and is particularly associated with the pathogenesis of cardiovascular disease. We undertook to investigate the association of obesity and the risk of AKI development following cardiac surgery. Methods: 432 patients who underwent cardiac surgery with cardiopulmonary bypass between October 2009 and August 2010 were included in the final retrospective analysis. Obesity was defined as BMI ≥ 30 kg/m 2 . Acute kidney injury (AKI) was defined as a creatinine increase of ≥ 25% from baseline at 48 h post surgery. Results: The overall incidence of AKI was 29.9% (n = 129). The incidence of diabetes was significantly higher in the obese cohort (24.3 vs. 10.8% p = 0.0005). There was an increased incidence of post-operative renal impairment in the obese vs. non-obese cohort, however this was not statistically significant (39 vs. 25.9%, p = 0.07). Univariate analysis of independent predictors of postoperative AKI revealed significant associations between obesity (BMI >30 kg/m 2 ) (OR 1.80, 95% CI 1.17–2.79, p = 0.01), cerebrovascular disease (OR 1.83, 95% CI 1.10–2.03, p = 0.02), hyperlipidaemia (OR 0.59, 95% CI 0.39–0.89, p = 0.02) and a history of smoking (OR 2.82, 95% CI 1.79–4.44, p < 0.0001). Multivariate logistic regression revealed that BMI >30 kg/m 2 was independently associated with the development of postoperative AKI (OR 1.81, 95% CI 1.11–2.95, p = 0.02) as were age (OR 0.98 95% CI 0.96–1.0, p = 0.03) and cardiopulmonary bypass time (OR 0.99, 95% CI 0.98–1.0, p = 0.03). Conclusion: Obesity ≥ 30 kg/m 2 is independently associated with an increased risk of AKI following cardiac surgery. Further understanding of the molecular basis of this association is critical to the design of preventative strategies.